2004
DOI: 10.2217/14750708.1.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sliding scale insulin use on glycemic control and length of stay in hospitalized patients with Type 2 diabetes mellitus

Abstract: Aim of this work was to asses whether a novel 99mTc labeled Bombesin (BN) can play a clinical role in diagnosis and staging of prostate cancer. 14 patients were studied with trans-rectal ultrasonography-guided biopsy, CT and MRI and with 99mTc BN Scintigraphy. Five patients were also imaged by 111In Octreotide (O) scan. All the patients but one were submitted to surgery and final diagnosis was reached by pathology, taken as the gold standard method. Two patients showed benign adenoma and 12 patients showed can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…This is consistent with previous studies, which generally examined more than 70% of hospitalized patients being treated with SSI [9,10]. Again, our data confirm that the use of a standing antidiabetic regimen, insulin and/or hypoglycemic agents, generally resulted in better glycemic control.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with previous studies, which generally examined more than 70% of hospitalized patients being treated with SSI [9,10]. Again, our data confirm that the use of a standing antidiabetic regimen, insulin and/or hypoglycemic agents, generally resulted in better glycemic control.…”
Section: Discussionsupporting
confidence: 92%
“…Data from our group and others [9,10,14] have shown, that the use of SSI resulted in significantly higher intra-hospital glycemia. SSI is usually practiced by housestaff physicians and generally transmitted as a tradition among trainees [11,12,14].…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Radiopharmaceuticals containing bombesin or its analogues, labeled with 99 mTechnetium, have been developed to target GRPR-expressing tumors for nuclear imaging, mainly with SPECT. Limited clinical studies have shown promise in detecting primary prostate cancer, nodal and bone metastases [58; 59]. Other labeling methods to obtain agents suitable for PET imaging are currently underway [60].…”
Section: Other Targetsmentioning
confidence: 99%